MEASURING THE RESEARCH EFFICIENCY OF UNIVERSITI TEKNOLOGI MARA (UITM) BY USING DATA ENVELOPMENT ANALYSIS (DEA): A CASE STUDY IN UITM PERLIS - Anas Fathul Ariffin,; Muhammad Amir Azahari,; Mohd Halimi Ab Hamid,; Teoh Yeong Kin,; Muhammad Hilmi Samian, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This paper aims to measure research efficiency of UiTM Perlis by using two different models, which are the Charnes, Cooper, and Rhodes (CCR) model and the Banker, Charnes, and Cooper (BCC) model. The data used is secondary data started from 2018 to 2022, obtained from the departments involved such as the Academic Affairs Division (HEA); Industry, Community, and Alumni Network (ICAN) Office, and Administration Office, UiTM Perlis. It has also been distinguished the competencies for each year and examined the current trends towards 2025, with the aim of achieving the mission of the UiTM2025 strategic plan. There are five decision making units (DMU's) for both aspects studied; 2018, 2019, 2020, 2021, and 2022, which are the five distinguished years for this study. The use of the two models in this study, namely CCR-I and BCC-I is to ensure that the ranking analysis results are more accurate and precise. Both models use input-oriented model functions as a way of maximizing efficiency in order to increase the number of fairies. For research efficiency, two DMU’s which is 2018 and 2020, were ranked first for both models. Thus, making this DMU's ranked first for both models.